Succinyl-β-cyclodextrin: Influence of the substitution degree on albendazole inclusion complexes probed by NMR - Priotti, Josefina (2018)
Succinyl-β-CD derivatives were obtained by green synthesis with degrees of substitution (DS) 1.3 and 2.9. The spray-drying technique was used to obtain albendazole (ABZ):succinyl-β-CD inclusion complexes. Phase solubility diagrams indicated that both succinyl-β-CD derivatives formed 1:1 molar ratio ABZ complexes, but the complex with DS 2.9 has a lower formation constant. The presence of stable inclusion complexes in aqueous solution was confirmed by NMR. For both complexes the aromatic moiety is encapsulated into the host cavity. In the solid-state, 13C and 15N NMR spectral differences between ABZ and ABZ included in spray-dried systems showed that strong structural changes occurred in the systems. At least two different ABZ amorphous species were identified based on DS. ABZ species were stable over more than six months based on spectral data. Finally, the influence of DS in the number and type of the inclusion complexes was elucidated.